Demographic Characteristics and the Performance of Supervisors of Swallowing Drugs in Parepare, Indonesia - Syarifuddin Syarifuddin; Chatarina Umbul Wahyuni; Soenarnatalina Melaniani (Health Notions, 2018)
2, 3 1(CA), Indonesia;  (Corresponding Author) 2, Indonesia 3, Indonesia ABSTRACT Pulmonary tuberculosis is a disease of global concern. This research was carried out in the work area of the City Health Center in Parepare, South Sulawesi, Indonesia. The purpose of this study was to analyze the influence of characteristics of supervisors swallowing drugs participants including demographic characteristics (age, sex, education, socio-economic), knowledge, attitudes and practices; on the performance of "supervisors swallowing drugs" in an effort to build adherence to patients with pulmonary tuberculosis in the treatment process, using a cross sectional design. The population of this study were all "drug swallowing supervisors" in the Parepare City Health Center Work Area, South Sulawesi, Indonesia. The sample in this study were 88 people selected by purposive sampling technique. Data on the characteristics of respondents, knowledge, attitude and practice were collected through questionnaires. After being collected, the data were analyzed by using logistic regression test. Based on the results of the study it was concluded that the performance of supervisors swallowing drugs related to work status. Keywords: Tuberculosis, Supervisors swallowing drugs